Mitral Valve Blood Cyst in a Pediatric Patient - Oğuzhan Kayar; Neziha Öz; Süleyman Sunkak; Mustafa Argun (Journal of Anatolian Medical Research, 2026)
Intracardiac blood cysts mostly located in the heart valves. Most patients are asymptomatic. However, it has been claimed that it may be associated with mitral valve insufficiency, left ventricular outflow tract obstruction, and even stroke in some rare cases, especially in adults. There is no consensus on its treatment. However, in cases with negative effects on heart functions, resection of the lesion is performed with low-risk surgical procedures.We decided to follow up our case of mitral valve blood cyst, which we detected incidentally, because it was asymptomatic and this lesion did not have a negative effect on heart functions.